Environmental control for plants on Earth and in space. - Albright, L.D.
Plant production systems have become more sophisticated. Climate control has changed over the past several decades from manual to digital operations, and control computers have become faster and more capable. The paper focuses first on the environment control of plant production in commercial greenhouses and plant growth chambers, and then contrasts that growing system with the needs for rather different control strategies to grow plants in space applications. To demonstrate key characteristics of greenhouse environment control, a nonlinear controller for coupled air temperature and humidity, with various methods of feedback and feedforward control appropriate for this system, is presented
Keywords: Agriculture; Climate control; Commercial greenhouse; Environmental control; Feedback; Feedforward; Humidity control; Intelligent control; Nonlinear control systems; Plant growth chambers; Plant production systems; Temperature control